A Survey of Bluetongue Infection and Associated Risk Factors among the One-Humped Camel (Camelus dromedaries) in Gadarif State, Eastern Sudan - Hatim H. Abraheem; Amira M. Elhassan; Mohammed O. Hussien; Khalid A. Enan; Azza B. Musa; Abdel Rahim M. El Hussein (Veterinary Medicine International)
Bluetongue (BT) is an infectious, noncontagious, vector-borne viral disease that affects wild and domestic ruminants transmitted by Culicoides spp. A cross-sectional study was carried out during the period 2016-2017 in Gadarif state. A total of 276 sera samples were collected from camels in six localities of Gadarif state, eastern Sudan, to investigate bluetongue virus (BTV) seroprevalence and associated risk factors of BTV infection including age, sex, breed, locality, and ecology of the region. Enzyme-linked immunosorbent assay (ELISA) was used for estimation of BTV seroprevalence rate. The overall BTV seroprevalence rate was 96.7% in the study area ranging from 93.5% to 100% in six screened localities with no significant differences. The findings revealed similar BTV seroprevalence rates in both males and females, but high rates were found in age group of less than one year and two to three years with estimated 100%. However, the lowest seroprevalence was found in the age group of five to four years with estimated BTV to be 92.3%. BTV seropositivity was not found to be statistically associated with examined different camel breeds which revealed 93%, 94.4%, 97.6%, and 97.8% seroprevalence in Bushari, Rashide, Arabi, and Anafi, breeds, respectively. Epidemiology of BTV assessment according to the ecology of the area showed high BTV seroprevalence in desert and savanna with estimated 100% and lower BTV seroprevalence in arid and rich savanna with estimated 94.8% and 95.7%, respectively. There was no significant association between BTV ELISA positivity and sex, breed, and ecology of the area.